PENGARUH INTENSITAS KONSUMSI CONTENT DIGITAL TRIVIAL PLATFORM TIKTOK TERHADAP PERKEMBANGAN KOGNITIF SISWA KELAS VIII SMP NEGERI 2 MASARAN TAHUN PELAJARAN 2025/2026 - Rujito, Bambang; Ersta Kusumaningtyas, Lydia; Dwi Sholikhah, Linda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examined the effect of trivial digital content consumption intensity on the TikTok platform on the cognitive development of eighth-grade students at SMP Negeri 2 Masaran in the 2025/2026 academic year. Using a quantitative ex post facto design, data were collected from 159 respondents selected via cluster sampling from a population of 254 students across five classes. A self-developed questionnaire, validated for reliability (Cronbach's Alpha of 0.870 for consumption intensity and 0.909 for cognitive development), measured cognitive development across three aspects: attention, memory, and executive function. Simple linear regression, conducted after classical assumption testing, revealed a significant negative effect of consumption intensity on cognitive development (F = 54.190, p = 0.000), with the independent variable explaining 25.8% of the variance (R² = 0.258) and a regression coefficient of -0.677, indicating that higher consumption intensity corresponds to lower cognitive development. This negative effect was also significant for each cognitive aspect individually: attention (R² = 0.211), memory (R² = 0.198), and executive function (R² = 0.227). These findings underscore the need for improved digital literacy and active parental and teacher guidance in students' social media use. Keywords: trivial digital content, TikTok, cognitive development, consumption intensity, junior high school students